Peircean Seeds for a Philosophy of Art - Ibri, Ivo A. (2012)
It is well known by the scholars on Peirce's philosophy that he didn't leave, among his huge work, something like a 'philosophy of art'. Notwithstanding this fact, I claim that Peirce's philosophy is composed of a system of ideas based on which it is possible to conceive a conceptual framework that will constitute a very original reflection on art. This originality comes, I believe, from the main metaphysical guidelines of his thought, namely, his realism – idealism, whose synthesis can be considered his theory of continuity or synechism. Semiotics, albeit a normative science, needs to take into account a dialog between sign forms and object forms, to be harmonious with the central hypothesis of synechism. Semiotics, therefore, cannot be confined to the sign universe in its normative task. This dialogy between sign and object will forbid a nominalistic understanding of that task; in other words, Semiotics generality will not rise from any hypothesis of transcendentality, neither can it be a source for a language foundation of the world. These considerations have capital importance for the foundations of a philosophy of art inspired in Peirce's philosophy, as it could not be a reductionist analysis of 'art language' or a mere apology of 'human creativity'. Therefore, this essay will develop the basic guidelines that could be, I suppose, a Peircean philosophy of art, based on the seeds he left for a reflection on the subject.